Editor's Choice - A Randomized Controlled Trial of the Fascia Suture Technique Compared with a Suture-mediated Closure Device for Femoral Arterial Closure after Endovascular Aortic Repair. Issue 2 (February 2015) - Larzon, T.; Roos, H.; Gruber, G.; Henrikson, O.; Magnuson, A.; Falkenberg, M.; Lönn, L.; Norgren, L.
Abstract : Objectives: The aim was to investigate whether the fascia suture technique (FST) can reduce access closure time and procedural costs compared with the Prostar technique (Prostar) in patients undergoing endovascular aortic repair and to evaluate the short- and mid-term outcomes of both techniques. Methods: In this two center trial, 100 patients were randomized to access closure by either FST or Prostar between June 2006 and December 2009. The primary endpoint was access closure time. Secondary outcome measures included access related costs and evaluation of the short- and mid-term complications. Evaluation was performed peri- and post-operatively, at discharge, at 30 days and at 6 months follow up. Results: The median access closure time was 12.4 minutes for FST and 19.9 minutes for Prostar ( p  < .001). Prostar required a 54% greater procedure time than FST, mean ratio 1.54 (95% CI 1.25–1.90, p  < .001) according to regression analysis. Adjusted for operator experience the mean ratio was 1.30 (95% CI 1.09–1.55, p  = .005) and for patient body mass index 1.59 (95% CI 1.28–1.96, p  < .001). The technical failure rate for operators at proficiency level was 5% (2/40) compared with 28% (17/59) for those at the basic level ( p  = .003). The proficiency level group had a technical failure rate of 4% (1/26) for FST and 7% (1/14) for Prostar, p  = 1.00, while corresponding rates for the basic level group were 27% (6/22) for FST and 30% (11/37) for Prostar ( p  = .84). There was a significant difference in cost in favor of FST, with a median difference of €800 (95% CI 710–927, p  < .001). Conclusions: In aortic endovascular repair FST is a faster and cheaper technique than the Prostar technique.